IMPLEMENTASI PENILAIAN PSIKOMOTOR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Sudriman Sudirman (IAIN Batusangkar, 2016)
In this qualitative study, the researcher described the implementation of psychomotor assessment for Islamic Education and Character Subject in State Islamic Secondary School Kajai Sei Rotan South Pariaman. The observation, documentation and interview were used on collecting data. The data were analyzed by applying data reduction, data display and data conclusion. The result showed that the psychomotor assessment had used the principles of assessment but was not perfect because of limited time, limited teacher, and limited teachers’ knowledge.Kata Kunci: Psychomotor Assessment, Islamic Education and Character Subject, State Islamic Secondary School, Kajai South Pariaman